Characterization by IRM and EMG of the muscles involved in pedalling in professional cyclists - Hug, F.; Bendahan, D.; Savin, B.; Cozzone, P.; Grelot, L. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Introduction Studies analysing the pattern of activity of the muscles implied in pedalling were carried out on sedentary subjects or non elite cyclits (Eisner et al., 1999; Ericson et al., 1986). They do not reveal any interindividual difference in the use of the various muscles and are often limited to the use of a single technique of analysis: the surface electromyograpy (EMG). EMG has been used for many years for characterizing the muscular electrical activity in numerous sports. In addition, the Magnetic Resonance Imaging (MRI) permits a non-invasive functional exploration of muscles function. Thus, the analysis of the changes (before versus after exercise) of contrast (T2 type) makes it possible to determine the active muscles during an exercise. The amplitude of these changes is correlated to the exercise intensity (Fisher et al., 1990). In the present series of experiments performed on professional cyclists, we combined these two noninvasive techniques to study the pattern of activity of lower limb muscular groups during exhausting pedalling exercises. Our experimental approach allows to determine wether or not the expert cyclists use a common pattern of recruitment for these muscles during pedalling. Methods Six professional cyclists participated to this study.